Determining suitable funding for p-12 education in Kansas: superintendents’ opinions and selected cost simulations - Clark, Rustin (Kansas State University, 2006)
The purpose of this study was to determine what school leaders believe is a suitable funding level for Kansas school districts and to simulate the effect and cost of selected findings. More specifically, three questions were examined: How much money do top leaders in each school district in Kansas believe is needed to provide a suitable education for all students in their school district? What would be a suitable per-pupil funding level for districts when examined by varying enrollment sizes if based on the perceived needs of school district leaders in Kansas? And, what would be the statewide cost to implement a suitable per-pupil funding level for districts of varying sizes based on the expressed needs of school district leaders in Kansas? To accomplish its purpose, the study was carried out in three phases. First, it examined research in the areas of school finance equity and adequacy, both of which influence how much money is distributed to schools. Second, this study surveyed top school district leaders in Kansas in search of their opinions regarding how much money is needed to provide an adequate and suitable education. Third, survey data provided the basis for selected simulations designed to estimate the effect and cost of proposed changes on individual school districts and the state of Kansas. The results of this study show that school district leaders widely believe more money is needed to meet performance mandates for regular education students, at-risk students, and bilingual students. When considering only regular education students, this study found that school leaders believe the state of Kansas is underfunding schools by $577 million. In addition, this study shows that at-risk students need an additional $246.6 million to be provided an adequate education, while bilingual student show nearly another $18 million of need. Some school districts in Kansas have managed to offset the perceived under-funding by utilizing local tax options beyond base state funding. These local options, however, are subject to voter approval and lead to concern by some over equitable and adequate funding for all school districts in Kansas.
Keywords: Education Finance; Kansas Education; Adequate Funding; Funding Formula; Superintendent Opinion; Education, Administration (0514); Education, Finance (0277)